Psychosocial Interventions and Social Support for Maternal Mental Health and the Prevention of Postpartum Depression: A Literature Review - Silvya Jeny Prasanty; Ernawati Ernawati (Newinera Publisher, 2025)
Postpartum depression is a significant public health issue that adversely affects maternal well-being and infant development. Psychological, hormonal, and social changes during pregnancy and the postpartum period increase women’s vulnerability to depressive symptoms, particularly when psychosocial support is inadequate. This study aimed to systematically review the evidence on psychosocial interventions for the prevention and reduction of postpartum depression among pregnant women in the third trimester and women in the postpartum period. A systematic literature review was conducted following the PRISMA guidelines. Articles were retrieved from Scopus, PubMed, and Garuda databases, limited to publications between 2020 and 2025. Ten studies met the inclusion criteria, encompassing randomized controlled trials, quasi-experimental studies, systematic reviews, meta-analyses, and qualitative meta-syntheses. The reviewed studies examined various psychosocial approaches, including digital and app-based interventions, psychoeducation and psychological self-help programs, as well as social and family support–based interventions. Overall, the findings indicate that psychosocial interventions are effective in reducing postpartum depressive symptoms and improving secondary mental health outcomes such as anxiety, stress, emotional well-being, and self-efficacy. Social support from partners, family members, and supportive healthcare environments emerged as a key protective factor that enhances intervention effectiveness. Digital interventions showed moderate but significant effects and offer advantages in accessibility and scalability. In conclusion, preventing postpartum depression requires a multidimensional and culturally sensitive approach that integrates psychosocial interventions with strengthened social support systems to promote sustainable maternal mental health outcomes.